Analisis Efektivitas Kelembagaan Kesatuan Pengelolaan Hutan Produksi (KPHP) Tebo Timur Unit X: Analysis of the Effectiveness of the TeboTimur Production Forest Management Unit (KPHP) Institution Unit X - Haryani, Haryani; Ahyaudin, Ahyaudin (Fakultas Kehutanan Universitas Jambi, 2023)
ABSTRACT KPH is an organization that works at the site level and is expected to be a prerequisite for the implementation of a sustainable and just forest management system. The purpose of this study was to analyze the level of institutional effectiveness and determine the driving and inhibiting factors in the management of KPHP Tebo Timur Unit X. The sampling method used was purposive sampling method with 29 informants sampled. This type of research uses quantitative and qualitative approaches. In data analysis, the method used is a combined method of quantitative and qualitative data analysis, namely semi-structured interviews (questionnaires) and tested with a Likert scale. The results of the analysis show that the level of institutional effectiveness in KPHP Tebo Timur Unit X is in the fairly effective category. The driving factors in KPHP management are the high motivation of the community towards social forestry, easy accessibility, support from related agencies and the existence of references in forest management plans. Keywords: KPH, effectiveness, institutional, driving factors, prevention factors. ABSTRAK KPH adalah organisasi yang berkerja di tingkat tapak dan diharapkan menjadi prasyarat dari terlaksananya sistem pengelolaan hutan yang lestari dan berkeadilan. Tujuan dari penelitian ini adalah untuk menganalisis tingkat efektivitas kelembagaan dan mengetahui faktor-faktor pendorong serta penghambat dalam pengelolaan KPHP Tebo Timur Unit X. Metode pengambilan sampel dengan menggunakan metode Purposive Sampling dengan 29 informan yang dijadikan sampel. Jenis penelitian ini menggunakan pendekatan kuantitatif dan kualitatif. Dalam analisis data metode yang digunakan yaitu metode gabungan antara analisis data kuantitatif dan kualitatif yaitu dengan wawancara semi terstruktur (kuesioner) dan diuji dengan skala likert. Hasil analisis menunjukkan bahwa tingkat efektivitas kelembagaan di KPHP Tebo Timur Unit X tergolong dalam kategori cukup efektif. Adapun faktor pendorong dalam pengelolaan KPHP adalah motivasi yang tinggi dari masyarakat terhadap perhutanan sosial, kemudahan aksesbilitas, adanya dukungan dari instansi terkait dan adanya acuan dalam rencana pengelolaan hutan. Kata kunci: KPH, efektivitas, kelembagaan, faktor pendorong, faktor penghambat